Tfh cells with NLRP3 inflammasome activation are essential for high-affinity antibody generation, germinal centre formation and autoimmunity - Zhao, Zhenhuan; Xu, Bihua; Wang, Shuang; Zhou, Mianjing; Huang, Yuefang; Guo, Chaohuan; Li, Mengyuan; Zhao, Jijun; Sung, Sun-Sang J; Gaskin, Felicia; Yang, Niansheng; Fu, Shu Man (Annals of the rheumatic diseases, 2022)
ObjectiveNLRP3 inflammasome regulates T cell responses. This study examined the roles of NLRP3 inflammasome activation in the regulation of T follicular helper (Tfh) cells during humoral response to T dependent antigens and in systemic lupus erythematosus (SLE).MethodsNLRP3 inflammasome activation of Tfh cells was studied in B6, MRL/lpr and NZM2328 mice and in SLE patients and healthy controls using a fluorescence-labelled caspase-1 inhibitor probe. MCC950, a selective inhibitor of NLRP3, was used to investigate the relation between NLRP3 inflammasome activation and germinal centre (GC) reaction, Ab responses to immunisation, and autoantibody production.ResultsNLRP3 inflammasome activation in Tfh cells after immunisation was identified in B6 mice. MCC950 inhibited humoral responses to sheep red blood cell and NP-CGG with reduction of the GC reaction. B6 mice with lymphoid cell-specific deletion of NLRP3 or Casp1 mounted suboptimal humoral responses with impaired GC formation and defective affinity maturation. In MRL/lpr and NZM2328 mice, inhibition of NLRP3 activation suppressed NLRP3 activated Tfh cell expansion as well as attenuated lupus-like phenotypes. Tfh cells with activated NLRP3 inflammasome exhibited increased expression of molecules for Tfh cell function and differentiation, and had greater ability to activate B cells. In SLE patients, disease activity was positively correlated with an increase in the activated NLRP3+ Tfh population and this population was markedly reduced in response to therapy.ConclusionsThe activation of NLRP3 inflammasome in Tfh cells is an integral part of responses to immunisation. The activated NLRP3+ Tfh population is essential for optimal humoral responses, GC formation and autoimmunity.